OPTIMIZATION OF ANTIBACTERIAL THERAPY FOR RESPIRATORY DISEASES IN CHILDREN UNDER 5 YEARS: A COMPREHENSIVE PHARMACOECONOMIC ABC ANALYSIS - Mavlyanova N.T. (Bright Mind Publishing, 2025)
This article presents a comprehensive ABC analysis of the utilization patterns of antibacterial drugs (ABDs) in the treatment of bronchopulmonary diseases among children under 5 years of age. Conducted across two distinct clinical departments of the Tashkent Pediatric Medical Institute, this study employed a retrospective pharmacoeconomic methodology, analyzing medical records of pediatric patients hospitalized between January and March 2024. The primary objective was to categorize ABDs based on their frequency of prescription and associated financial burden, thereby identifying key drivers of clinical expenditure and prescribing habits. The ABC analysis successfully delineated high-priority medications, contributing valuable insights for optimizing pharmacotherapy and promoting the rational allocation of clinical resources. The findings revealed notable disparities in the prescription structures between the observed departments, underscoring the absence of a unified therapeutic protocol. These variations highlight an urgent need for the revision and standardization of treatment guidelines to ensure both clinical efficacy and economic sustainability. Furthermore, this research underscores the critical role of continuous antimicrobial stewardship in pediatric settings to mitigate the escalating threat of antibiotic resistance, improve patient outcomes, and reduce unnecessary healthcare costs.
Keywords: ABC analysis, antibacterial drugs, bronchopulmonary diseases, pediatrics, children under 5, pharmacoeconomics, antibiotic stewardship, respiratory infections, cost optimization.